Undercover Feminist Pedagogy in Information Literacy: A Literature Review - Kingsland, Emily (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2020)
Objective – Feminist pedagogy in library instruction presents a new approach to actively engaging students in the research process. While feminist pedagogy in universities found early adoption in the 1970s, it is a newer phenomenon in library instruction, finding its early roots in works by Ladenson (2010), Accardi (2010), and Accardi and Vukovic (2013).By fostering active engagement and critical thinking skills, feminist library instruction sessions encourage students to question authority, actively participate in the knowledge production process, and become aware of their power and information privilege as they navigate increasingly complex information environments. At its core, this specific pedagogical approach subverts traditional classroom dynamics by focusing on diversity and inclusion.This literature review demonstrates how feminist pedagogy is currently being practiced in academic library information literacy sessions and how students can be assessed in a feminist manner.Methods – Practitioners of feminist pedagogy draw on techniques and methodologies designed to emphasize and value different experiences, such as cooperative learning, collaborative learning, inquiry-based learning, and inquiry-guided learning. These techniques and methodologies are used to develop students’ information literacy skills, to take ownership of the research process, and to stimulate critical inquiry.For the literature review, the following databases were searched: Education Resources Information Center (ERIC) on the ProQuest platform; Library & Information Science Abstracts (LISA); Library, Information Science & Technology Abstracts (LISTA); Scopus; and Web of Science Core Collection. Hand searching in WorldCat, as well as cited reference searching and bibliography mining, were also conducted. The searches were run between November 2018 and April 2019, followed by a second round in July 2019 based on participant feedback from the 2019 EBLIP10 conference. Case studies, books, book chapters, literature reviews, research papers, interviews, surveys, and papers based on statistical and qualitative analysis were consulted.Results – While some librarians may lack familiarity with feminist theory, feminism writ large influences academic librarians’ professional practice (Schroeder & Hollister, 2014). Librarians can incorporate feminist pedagogy into their practice and assessment in many concrete ways. However, librarians who focus on feminist pedagogy may face obstacles in their teaching, which may explain why publications on feminist pedagogical discourse within library and information studies have emerged only within the last decade (Fritch, 2018; Hackney et al., 2018). The most common challenge feminist librarians face is the restrictive nature of the standalone, one-shot information literacy session. Moreover, there is much room for improvement in library and information studies programs to introduce students to the theory and practice of feminist pedagogy.Conclusion – This paper highlights examples of feminist methods librarians can put into practice in their information literacy sessions and ways in which students can be assessed in a feminist manner. The literature demonstrates that feminist pedagogy has been successfully implemented for decades in universities. By comparison, practicing feminist pedagogy at the library instruction level is a relatively new area of focus within the profession. Hopefully, this growing trend will lead to more evidence based literature in the near future.